Understanding Fatal and Non-Fatal Drug Overdose Risk Factors: Overdose Risk Questionnaire Pilot Study—Validation - Doggui, Radhouene; Adib, Keyrellous; Baldacchino, Alex (Frontiers in Pharmacology, 2021)
Background: Drug overdoses (fatal and non-fatal) are among the leading causes of death in population with substance use disorders. The aim of the current study was to identify risk factors for fatal and non-fatal drug overdose for predominantly opioid dependent treatment seeking population. Methods: Data were collected from 640 adult patients using a self-reported 25 item OdRi questionnaire pertaining to drug use and identified related domains. The Exploratory Factor Analysis (EFA) was primarily used to improve the interpretability of this questionnaire. Two sets of EFA were conducted, in the first set of analysis all items were included while in the second set items related to experience of overdose were removed. Linear regression was used for the assessment of latent factors association with both fatal and non-fatal overdose. Results: EFA suggested a three-factor solution accounting for 75% and 97% of the variance for items treated in the 1st and 2nd sets of analysis, respectively. Factor 1 was common for the both sets of EFA analysis, contained six items (Cronbach's alpha = 0.70) focusing around ‘illicit drug use and lack of treatment’. In the 1st set of analysis, Factors 2 (Cronbach's alpha = 0.60) and 3 (Cronbach's alpha = 0.34) were focusing around ‘mental health and emotional trauma’ and ‘chronic drug use and frequent overdose’ domains respectively. The increase of Factor 2 was found to be a risk factor for fatal drug overdose (adjusted coefficient=1.94, P=0.038). In the 2nd set of analysis, factors 2 (Cronbach's alpha = 0.65) and 3 (Cronbach's alpha = 0.59) as well as factor 1 were found to be risk factors for non-fatal drug overdose ever occurring. Only Factors 1 and 3 were positively associated with non-fatal overdose (one in a past year). Conclusion: The OdRi tool developed here could be helpful for clinical studies for overdose risk assessment. However, integrating validated tools for mental health can probably help to refine the accuracy of latent variables and the questionnaire's consistency. Mental health and life stress appear as important predictors of both fatal and non-fatal overdose.